Guidelines for Closing the Efficiency Gap between Hero Solar Cells and Roll‐To‐Roll Printed Modules. Issue 4 (24th March 2015) - Lucera, Luca; Kubis, Peter; Fecher, Frank W.; Bronnbauer, Carina; Turbiez, Mathieu; Forberich, Karen; Ameri, Tayebeh; Egelhaaf, Hans‐Joachim; Brabec, Christoph J.
Abstract: One of the biggest challenges for the commercialization of polymer‐based and other printed photovoltaic (PV) technologies is to establish reliable up‐scaling processes that minimize the efficiency losses occurring during the transition from record laboratory cells to roll‐to‐roll (R2R) printed PV modules. This article reviews the latest advances in reducing the efficiency gap between record solar cells and large‐area organic PV modules. The major loss sources are identified for the most popular cell architectures and categorized into optical, electrical, and processing‐related contributions. Their relative shares in the overall efficiency drop are quantified through optical and electrical simulations. Further potential sources of efficiency loss, such as the replacement of halogenated by green solvents for active layer processing, are also addressed. Finally, the effect of reduced efficiency gaps on the production costs of R2R printed modules is discussed, demonstrating that values as low as € 0.5 Wp −1 (the nominal power of a solar module/cell) can be achieved. Abstract : Solar hero: One of the biggest challenges for the commercialization of polymer‐based and other printed photovoltaic (PV) technologies is to establish reliable up‐scaling processes that minimize the efficiency losses occurring during the transition from record laboratory cells to roll‐to‐roll (R2R) printed PV modules. This article reviews the latest advances in reducing the efficiency gap between record solar cells and large‐area organic PV modules.